Influence of periodizing dietary carbohydrate on iron regulation and immune function in elite triathletes - McKay, A. K. A.; Heikura, I. A.; Burke, L. M.; Peeling, P.; Pyne, D. B.; van Swelm, R. P. L.; Laarakkers, C. M.; Cox. G. R. (International Journal of Sport Nutrition and Exercise Metabolism, 2020)
Sleeping with low carbohydrate (CHO) availability is a dietary strategy that may enhance training adaptation. However, the impact on an athlete`s health is unclear. This study quantified the effect of a short-term "sleep-low" dietary intervention on markers of iron regulation and immune function in athletes. In a randomized, repeated-measures design, 11 elite triathletes completed two 4-day mixed cycle run training blocks. Key training sessions were structured such that a high-intensity training session was performed in the field on the afternoon of Days 1 and 3, and a low-intensity training (LIT) session was performed on the following morning in the laboratory (Days 2 and 4). The ingestion of CHO was either divided evenly across the day (HIGH) or restricted between the high-intensity training and LIT sessions, so that the LIT session was performed with low CHO availability (LOW). Venous blood and saliva samples were collected prior to and following each LIT session and analyzed for interleukin-6, hepcidin 25, and salivary immunoglobulin-A. Concentrations of interleukin-6 increased acutely after exercise (p < .001), but did not differ between dietary conditions or days. Hepcidin 25 increased 3-hr postexercise (p < .001), with the greatest increase evident after the LOW trial on Day 2 (2.5 ± 0.9 fold increase ±90% confidence limit). The salivary immunoglobulin-A secretion rate did not change in response to exercise; however, it was highest during the LOW condition on Day 4 (p = .046). There appears to be minimal impact to markers of immune function and iron regulation when acute exposure to low CHO availability is undertaken with expert nutrition and coaching input.